Action research in marketing - Perry, Chad (European journal of marketing, 2004)
Develops a definition of action research that is particularly suitable for marketing and based on the articles in this issue of European Journal of Marketing, emphasising the breadth of action research in marketing and its distinctive interest in analytic generalisation, that is, in building a theory that extends beyond the particular situation that is being action researched to other situations. The three sections of this commentary include: definition of traditional action research, action learning and case research. Second, drawing of four implications from the articles within this special.